Ti2AlNb material weld crack sensitivity quantitative evaluation method

By quantitatively analyzing the weld crack data of Ti2AlNb materials under different welding speeds and heat treatment conditions, the problem of lack of quantitative evaluation methods in the prior art is solved, and the accurate evaluation of weld crack sensitivity and optimization of welding process is achieved.

CN119525676APending Publication Date: 2025-02-28AECC AVIATION POWER CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411693628.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art lacks an effective quantitative method for evaluating the crack sensitivity of the electron beam weld of Ti2AlNb material, which makes it difficult to guarantee the strength and reliability of the welded joints.

Method used

By adopting crack data of multiple sets of Ti2AlNb material plates under different welding speeds and heat treatment conditions, the number of microcracks at the cross section of the welded joint was counted using optical metallographic microscope, and the cross section crack frequency was calculated as a quantitative evaluation index for weld crack sensitivity.

Benefits of technology

Accurate quantitative evaluation of the weld crack sensitivity of Ti2AlNb material is achieved, which can comprehensively examine the impact of welding speed and heat treatment on crack sensitivity, optimize welding and heat treatment processes, reduce the generation of weld cracks, and improve the utilization rate of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119525676A_ABST
    Figure CN119525676A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of weld crack quantitative evaluation, and discloses a Ti2AlNb material weld crack sensitivity quantitative evaluation method, which comprises the following steps: respectively adopting crack data of a plurality of groups of Ti2AlNb material flat plates under different welding speeds and different heat treatments; respectively processing the crack data of the multiple groups of Ti2AlNb material flat plates under different welding speeds and different heat treatments to obtain crack sensitivity quantitative evaluation indexes under the welding parameters of the multiple groups of Ti2AlNb material flat plates under different welding speeds and different heat treatments; and comparing and analyzing the quantitative evaluation indexes of the crack sensitivity under the welding parameters of a plurality of groups of Ti2AlNb material flat plates at different welding speeds and different heat treatments to obtain a quantitative result of the crack sensitivity of the welding seam of the Ti2AlNb material. The number of microcracks at the section of a welding joint under different welding and heat treatment process parameters is counted through an optical microscope, the crack frequency is calculated by averaging the section crack frequency, and the weld section crack frequency serves as a quantitative evaluation index of the electron beam weld crack sensitivity of the Ti2AlNb material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of weld crack quantitative evaluation, and in particular to a Ti2AlNb material weld crack sensitivity quantitative evaluation method. Background Art

[0002] Ti2AlNb is an important lightweight high-temperature structural material in TiAl alloys, and its operating temperature range is usually 650-750℃. This material is based on Ti3Al intermetallic compound, and by adding a large amount of Nb elements, a new material with O phase (ordered orthorhombic system) as the main phase is formed. Ti2AlNb material has excellent comprehensive mechanical properties, including high specific strength, high fracture toughness, good room temperature plasticity and creep resistance, which makes it one of the most promising materials to replace Ni-based alloys.

[0003] However, Ti2AlNb materials have a high content of alloying elements and are very sensitive to thermal responses during welding. This causes the material to have a greater tendency to be brittle at high temperatures and is prone to weld crack defects. These crack defects not only reduce the strength and reliability of the welded joint, but may also have a serious impact on the overall quality and safety of the product. Therefore, eliminating weld crack defects is a major challenge in the welding process of Ti2AlNb materials.

[0004] At present, there is still a lack of an effective quantitative method for evaluating the crack sensitivity of electron beam welds of Ti2AlNb materials. Traditional evaluation methods often rely on macroscopic observation and empirical judgment, which cannot accurately reflect the true situation of weld crack sensitivity. In addition, due to the particularity of Ti2AlNb materials, the crack sensitivity under different welding process parameters may vary significantly, so there is an urgent need for a method that can accurately and quantitatively evaluate the crack sensitivity of welds. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a method for quantitatively evaluating the crack sensitivity of the weld of Ti2AlNb material, so as to solve the technical problem of how to quantitatively evaluate the crack sensitivity of the weld of Ti2AlNb material.

[0006] The present invention is achieved through the following technical solutions: A quantitative evaluation method for crack sensitivity of a Ti2AlNb material weld comprises: The crack data of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments were taken; The crack data of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments are processed respectively to obtain the quantitative evaluation index of crack sensitivity under welding parameters of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments; The quantitative evaluation indexes of crack sensitivity under multiple groups of Ti2AlNb material flat plate welding parameters at different welding speeds and different heat treatments were compared and analyzed to obtain the quantitative results of the crack sensitivity of the Ti2AlNb material weld.

[0007] Preferably, the specific process of taking multiple groups of crack data of Ti2AlNb material plates at different welding speeds is as follows: Electron beam welding process tests were carried out on multiple groups of Ti2AlNb material plates at different welding speeds, wherein multiple groups of standard specimens were taken at each welding speed, and the number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens was counted to obtain the cross-sectional crack frequency of each group of specimens.

[0008] Furthermore, the different welding speeds include 8 mm / s, 12 mm / s or 20 mm / s.

[0009] Further, the electron beam welding process test process is as follows: A Ti2AlNb material flat plate is selected as a welding test plate, and the welding test plate is placed in a vacuum system through a fixture; Evacuate the welding chamber and set welding parameters, including electron beam acceleration voltage, focusing current, welding beam current, and welding speed; Start the electron beam welding equipment and perform welding operations; After welding is completed, the electron beam welding equipment is turned off, the weld is allowed to cool naturally to room temperature, and the weld is observed. The number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens is counted to obtain the cross-sectional crack frequency of each group of specimens.

[0010] Furthermore, the cross-sectional crack frequency of each group of specimens was averaged and the average cross-sectional crack frequency was obtained as a quantitative evaluation index of crack sensitivity at different welding speeds.

[0011] Preferably, multiple groups of Ti2AlNb material flat plates are subjected to electron beam welding and heat treatment tests with different heat treatments, wherein multiple groups of standard specimens are taken under each heat treatment, and the number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens is counted to obtain the cross-sectional crack frequency of each group of specimens.

[0012] Further, different heat treatment parameters include 800°C / 4H / AC, 860°C / 2H / AC or 890°C / 4H / AC.

[0013] Further, the specific process of heat treatment electron beam welding and heat treatment test is as follows: Select multiple groups of Ti2AlNb material flat plates as test objects; According to the Ti2AlNb alloy phase diagram, solution treatment or aging treatment is performed; Use sandpaper, acetone, etc. to thoroughly clean the welding surface to remove oxide scale and oil impurities; The welding room is vacuumed, welding parameters are set, welding is completed in one process, and the welding is allowed to cool naturally after welding; After welding is completed, the number of cracks in the cross-sectional area of ​​the weld joint is observed to obtain the cross-sectional crack frequency of each group of specimens.

[0014] Furthermore, the cross-sectional crack frequency of each group of specimens was averaged and the average cross-sectional crack frequency was obtained as a quantitative evaluation index of crack sensitivity under different heat treatments.

[0015] Preferably, in the step of comparing and analyzing the quantitative evaluation indexes of crack sensitivity under multiple groups of Ti2AlNb material plate welding parameters under different welding speeds and different heat treatments to obtain the quantitative results of the crack sensitivity of the Ti2AlNb material weld, the specific analysis process is as follows: Microhardness measurement and analysis of welded joints under different welding parameters and different post-weld heat treatment systems are carried out. When the hardness under different welding parameters and any parameters of different post-weld heat treatment systems is compared, the highest hardness indicates that the parameter is the optimal welding parameter or the optimal post-weld heat treatment system parameter.

[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention provides a method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld. The method comprises the following steps: using an optical metallographic microscope to count the number of microcracks at a cross section of a weld joint under different welding and heat treatment process parameters, taking an average value of the cross section crack frequency to calculate the crack frequency, and taking the weld cross section crack frequency as a quantitative evaluation index for the crack sensitivity of an electron beam weld of the Ti2AlNb material.

[0017] Furthermore, by taking multiple sets of crack data of Ti2AlNb material plates under different welding speeds and different heat treatments, the influence of welding speed and heat treatment on the crack sensitivity of Ti2AlNb material welds can be comprehensively and systematically examined. By processing and analyzing these data, quantitative evaluation indicators of crack sensitivity under different welding speeds and heat treatment conditions can be obtained, thereby achieving an accurate assessment of the crack sensitivity of Ti2AlNb material welds.

[0018] Furthermore, the use of an optical metallographic microscope to observe the cross section of the welded joint can accurately count the number of microcracks, avoiding the errors that may be caused by macroscopic observation. By calculating the crack frequency, that is, the number of cracks per unit area or unit length, the crack sensitivity of the Ti2AlNb material weld can be more accurately reflected, providing reliable data support for subsequent welding process optimization and material selection.

[0019] Furthermore, Ti2AlNb material, as a lightweight high-temperature structural material, has broad application prospects in aerospace, energy and other fields. However, due to its poor weldability, traditional welding methods often lead to cracks in the weld, reducing the utilization rate of the material. This method can provide a more reliable basis for the welding of Ti2AlNb materials by quantitatively evaluating the crack sensitivity of the weld, thereby reducing the generation of weld cracks and improving the utilization rate of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The present invention is a flow chart of the quantitative evaluation method for the crack sensitivity of the Ti2AlNb material weld. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0022] The purpose of the present invention is to provide a method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld, so as to solve the technical problem of how to quantitatively evaluate the crack sensitivity of a Ti2AlNb material weld.

[0023] The present invention is further described in detail below in conjunction with the accompanying drawings: See also Figure 1 The present invention provides a method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld, comprising: Step 1, respectively obtaining multiple groups of crack data of Ti2AlNb material plates under different welding speeds and different heat treatments; Specifically, the specific process of taking multiple sets of crack data of Ti2AlNb material plates at different welding speeds is as follows: Electron beam welding process tests were carried out on multiple groups of Ti2AlNb material plates at different welding speeds, wherein multiple groups of standard specimens were taken at each welding speed, and the number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens was counted to obtain the cross-sectional crack frequency of each group of specimens.

[0024] The different welding speeds in the present invention include 8 mm / s, 12 mm / s or 20 mm / s.

[0025] Specifically, the electron beam welding process test process is as follows: A Ti2AlNb material flat plate is selected as a welding test plate, and the welding test plate is placed in a vacuum system through a fixture; Evacuate the welding chamber and set welding parameters, including electron beam acceleration voltage, focusing current, welding beam current, and welding speed; Start the electron beam welding equipment and perform welding operations. During the welding process, the welding position and beam deviation distance can be adjusted according to actual conditions to ensure the quality of the weld.

[0026] After welding is completed, the electron beam welding equipment is turned off, the weld is allowed to cool naturally to room temperature, and the weld is observed. The number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens is counted to obtain the cross-sectional crack frequency of each group of specimens.

[0027] After welding is completed, use optical microscope, scanning electron microscope and other equipment to observe and analyze the microstructure of the weld area to determine the phase composition, grain size, morphology and other characteristics of the weld.

[0028] Among them, the cross-sectional crack frequency of each group of samples is averaged and the average cross-sectional crack frequency is obtained as a quantitative evaluation index of crack sensitivity under different welding speeds.

[0029] Step 2, respectively processing the crack data of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments to obtain quantitative evaluation indicators of crack sensitivity under welding parameters of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments; Specifically, multiple groups of Ti2AlNb material flat plates were subjected to electron beam welding and heat treatment tests with different heat treatments, wherein multiple groups of standard specimens were taken under each heat treatment, and the number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens was counted to obtain the cross-sectional crack frequency of each group of specimens.

[0030] The different heat treatment parameters include 800°C / 4H / AC, 860°C / 2H / AC or 890°C / 4H / AC.

[0031] Specifically, the specific process of heat treatment electron beam welding and heat treatment test is as follows: Select multiple groups of Ti2AlNb material flat plates as test objects; According to the Ti2AlNb alloy phase diagram, solution treatment or aging treatment is performed; In the solution treatment, the temperature is raised to 940-970°C at a rate of 10°C / min, kept at this temperature for 1.5 hours, and then water-cooled. This step helps to eliminate the stress inside the material and optimize its microstructure.

[0032] In the aging treatment, the temperature is raised to 800-830℃ at a rate of 10℃ / min, kept at this temperature for 24 hours, and then air-cooled. Aging treatment can further stabilize the organizational structure of the material and improve its mechanical properties.

[0033] Use sandpaper, acetone, etc. to thoroughly clean the welding surface to remove oxide scale and oil impurities; Use special fixtures to assemble and fix the workpieces to be welded, adjust the position so that the welding surfaces fit closely, the maximum fitting clearance of the weld should be controlled within 0.1mm, and the step difference should not be greater than 10% of the parent material.

[0034] The welding room is vacuumed, welding parameters are set, welding is completed in one process, and the welding is allowed to cool naturally after welding; After welding is completed, the number of cracks in the cross-sectional area of ​​the weld joint is observed to obtain the cross-sectional crack frequency of each group of specimens.

[0035] After welding, the weld appearance quality is visually inspected to ensure that the weld is flat and smooth, without defects such as cracks, incomplete penetration, lack of fusion and undercut.

[0036] Among them, the average cross-sectional crack frequency of each group of samples is calculated to obtain the average cross-sectional crack frequency as a quantitative evaluation index of crack sensitivity under different heat treatments.

[0037] Step 3, comparative analysis of the crack sensitivity quantitative evaluation indexes under multiple groups of Ti2AlNb material flat plate welding parameters at different welding speeds and different heat treatments is performed to obtain the quantitative results of the crack sensitivity of the Ti2AlNb material weld.

[0038] Specifically, microhardness measurement and analysis are performed on weld joints under different welding parameters and different post-weld heat treatment systems. When the hardness under different welding parameters and any parameters of different post-weld heat treatment systems is compared, the highest hardness indicates that the parameter is the optimal welding parameter or the optimal post-weld heat treatment system parameter.

[0039] The specific process of the present invention at different welding speeds is as follows: The electron beam welding process test of Ti2AlNb material at different welding speeds was carried out. Before welding, Ti2AlNb material was in solid solution state, the thickness of the plate was 10mm, and the plate butt joint was used for electron beam welding verification. After welding, SEM was used to observe the number of microcracks in the cross section of the electron beam welded joint. The cross-sectional size of the joint was 1cm×1cm. Ten welded cross sections were taken for statistics at each welding speed to obtain the number of cracks in the electron beam welded joint at different welding speeds. The average cross-sectional crack frequency was taken as the weld crack frequency under the welding parameters.

[0040] The specific process of the present invention under different post-weld heat treatment systems is as follows: The electron beam welding process test of Ti2AlNb material under different post-weld heat treatment systems was carried out. Before welding, the Ti2AlNb material was in solid solution state, the thickness of the plate was 10mm, and the plate was butt-jointed for electron beam welding. After welding, different post-weld heat treatment systems were adopted. After heat treatment, SEM was used to observe the number of microcracks in the cross section of the electron beam welded joint. The cross-sectional size of the joint was 1cm×1cm. Ten welded cross sections were taken for statistics under each heat treatment system to obtain the number of cracks in the electron beam welded joint under different heat treatment systems. The average cross-sectional crack frequency was taken as the weld crack frequency under the heat treatment system.

[0041] The quantitative evaluation indexes of crack sensitivity under different welding speeds and heat treatments of multiple groups of Ti2AlNb material plate welding parameters were compared and analyzed to obtain the quantitative results of the crack sensitivity of the Ti2AlNb material weld. The specific process is as follows: Hardness tests were carried out on electron beam welded joints of Ti2AlNb materials at different welding speeds and different post-weld heat treatment systems. Since there are a large number of 0 phase and α2 phase in the welded joints of Ti2AlNb materials, the presence of the two can achieve precipitation strengthening of the welded joints. Hardness tests were used to characterize the content of 0 phase and α2 phase and their strengthening effects, and further verify the resistance to crack propagation here.

[0042] The Ti2AlNb material in the present invention is a lightweight high-temperature structural material with broad application prospects in the fields of aerospace, energy, etc. However, due to its poor weldability, conventional welding methods often cause cracks in the weld, reducing the utilization rate of the material. The method can provide a more reliable basis for the welding of Ti2AlNb materials by quantitatively evaluating the sensitivity of weld cracks, thereby reducing the generation of weld cracks and improving the utilization rate of the material.

[0043] In summary, the present invention provides a quantitative evaluation method for the weld crack sensitivity of Ti2AlNb material, which quantitatively evaluates the crack sensitivity of the material by the weld crack frequency. It can explore the influence of different welding process parameters and different post-weld heat treatment systems on electron beam welded joints, and provide technical support for the optimization of Ti2AlNb material welding and heat treatment process parameters and the setting of post-weld preheating temperature.

[0044] Example 1 Electron beam welding experiments were carried out on multiple sets of Ti2AlNb material plates with specifications of (100×100×10) mm at different welding speeds (8 mm / s, 12 mm / s, and 20 mm / s, respectively).

[0045] At each welding speed, 10 groups of specimens with a specification of (10×10×10) mm were cut by wire cutting after welding.

[0046] SEM was used to observe and count the number of cracks in the cross-sectional area of ​​the weld joint (10×10) mm, and the crack frequency of each sample cross section was calculated (cross-sectional crack frequency = number of cracks in the weld joint ÷ cross-sectional area).

[0047] The average crack frequency of the cross section of 10 groups of specimens was taken as a quantitative evaluation index of crack sensitivity under the welding parameters.

[0048] Multiple groups of Ti2AlNb material plates with specifications of (100×100×10) mm were used for electron beam welding and heat treatment tests under different heat treatment systems (800℃ / 4H / AC, 860℃ / 2H / AC, 890℃ / 4H / AC).

[0049] Under each heat treatment system, 10 groups of specimens with a specification of (10×10×10) mm were cut by wire cutting.

[0050] SEM was used to observe and count the number of cracks in the cross-sectional area of ​​the weld joint (10×10) mm, and the crack frequency of each sample cross section was calculated (cross-sectional crack frequency = number of cracks in the weld joint ÷ cross-sectional area).

[0051] The average crack frequency of the cross section of 10 groups of specimens was taken as a quantitative evaluation index of crack sensitivity under the heat treatment parameters.

[0052] Microhardness measurement and analysis were carried out on welded joints under different welding parameters and different post-weld heat treatment systems. The results showed that under the parameters of 8 mm / s and 860 °C / 2H / AC, the microhardness was higher than that under other parameters, indicating that the strengthening effect of 0 phase and α2 phase was obvious, further verifying the crack sensitivity index in the examples in Table 1 and Table 2.

[0053] Table 1 Weld crack frequency at different welding speeds

[0054] Table 2 shows the weld crack frequency under different post-weld heat treatment systems

[0055] The present invention provides a method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld. The method comprises the following steps: using an optical metallographic microscope to count the number of microcracks at a cross section of a weld joint under different welding and heat treatment process parameters, taking an average value of the cross section crack frequency to calculate the crack frequency, and taking the weld cross section crack frequency as a quantitative evaluation index for the crack sensitivity of an electron beam weld of the Ti2AlNb material.

[0056] The present invention can comprehensively and systematically examine the influence of welding speed and heat treatment on the crack sensitivity of the weld of Ti2AlNb material by taking multiple groups of crack data of Ti2AlNb material plates under different welding speeds and different heat treatments. By processing and analyzing these data, quantitative evaluation indexes of crack sensitivity under different welding speeds and heat treatment conditions can be obtained, thereby realizing accurate evaluation of the crack sensitivity of the weld of Ti2AlNb material.

[0057] By comparing the crack frequencies under different welding and heat treatment process parameters, the present invention can intuitively understand the influence of these parameters on the crack sensitivity of the Ti2AlNb material weld. This helps engineers optimize the welding and heat treatment processes in actual production and select the best process parameter combination, thereby reducing the occurrence of weld cracks and improving the strength and reliability of the welded joint.

[0058] In key areas such as aerospace and energy, product quality and safety are of vital importance. This method can ensure that the welded joint meets the design requirements and reduce safety hazards caused by weld cracks by quantitatively evaluating the crack sensitivity of Ti2AlNb material welds. This helps to improve the overall quality and safety of products and enhance market competitiveness.

[0059] The research and application of this invention not only helps to solve practical problems in the welding process of Ti2AlNb materials, but also promotes the development of material science research. Through in-depth research on the crack sensitivity of welds, the welding mechanism and crack generation mechanism of materials can be further revealed, providing theoretical support for the development of new welding methods and materials.

[0060] By optimizing the welding and heat treatment processes and reducing the occurrence of weld cracks, the scrap rate and rework rate can be reduced, thereby improving production efficiency and economic benefits. In addition, this method can also provide more reliable welding process guidance for the application of Ti2AlNb materials, expand its application range, and further promote the development of related industries.

[0061] In summary, the quantitative evaluation method for the crack sensitivity of the weld of Ti2AlNb material provided by the present invention has multiple beneficial effects such as improving the evaluation accuracy, optimizing the welding and heat treatment process, improving the product quality and safety, promoting the research and development of materials science, and improving the production efficiency and economic benefits. This is of great significance for promoting the application of Ti2AlNb materials in the fields of aerospace, energy, etc.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A quantitative evaluation method for crack sensitivity of Ti2AlNb material weld, characterized in that: include The crack data of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments were taken; The crack data of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments are processed respectively to obtain the quantitative evaluation index of crack sensitivity under welding parameters of multiple groups of Ti2AlNb material plates under different welding speeds and different heat treatments; The quantitative evaluation indexes of crack sensitivity under multiple groups of Ti2AlNb material flat plate welding parameters at different welding speeds and different heat treatments were compared and analyzed to obtain the quantitative results of the crack sensitivity of the Ti2AlNb material weld.

2. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 1, characterized in that: The specific process of taking multiple sets of crack data of Ti2AlNb material plates at different welding speeds is as follows: Electron beam welding process tests were carried out on multiple groups of Ti2AlNb material plates at different welding speeds, wherein multiple groups of standard specimens were taken at each welding speed, and the number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens was counted to obtain the cross-sectional crack frequency of each group of specimens.

3. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 2, characterized in that: The different welding speeds include 8 mm / s, 12 mm / s or 20 mm / s.

4. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 2, characterized in that: The electron beam welding process test process is as follows: A Ti2AlNb material flat plate is selected as a welding test plate, and the welding test plate is placed in a vacuum system through a fixture; Evacuate the welding chamber and set welding parameters, including electron beam acceleration voltage, focusing current, welding beam current, and welding speed; Start the electron beam welding equipment and perform welding operations; After welding is completed, the electron beam welding equipment is turned off, the weld is allowed to cool naturally to room temperature, and the weld is observed. The number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens is counted to obtain the cross-sectional crack frequency of each group of specimens.

5. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 2, characterized in that: The average cross-sectional crack frequency of each group of specimens was calculated and the average cross-sectional crack frequency was used as a quantitative evaluation index of crack sensitivity at different welding speeds.

6. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 1, characterized in that: The method comprises the following steps: performing electron beam welding and heat treatment tests on multiple groups of Ti2AlNb material flat plates using different heat treatments, wherein multiple groups of standard specimens are taken under each heat treatment, and the number of cracks in the cross-sectional area of ​​the weld joint of each group of specimens is counted to obtain the cross-sectional crack frequency of each group of specimens.

7. A method for quantitatively evaluating crack sensitivity of a Ti2AlNb material weld according to claim 6, characterized in that: The different heat treatment parameters include 800° C. / 4H / AC, 860° C. / 2H / AC or 890° C. / 4H / AC.

8. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 6, characterized in that: The specific process of the heat treatment electron beam welding and heat treatment test is as follows: Select multiple groups of Ti2AlNb material flat plates as test objects; According to the Ti2AlNb alloy phase diagram, solution treatment or aging treatment is performed; Use sandpaper, acetone, etc. to thoroughly clean the welding surface to remove oxide scale and oil impurities; The welding room is vacuumed, welding parameters are set, welding is completed in one process, and the welding is allowed to cool naturally after welding; After welding is completed, the number of cracks in the cross-sectional area of ​​the weld joint is observed to obtain the cross-sectional crack frequency of each group of specimens.

9. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 6, characterized in that: The average cross-sectional crack frequency of each group of specimens was calculated and the average cross-sectional crack frequency was used as a quantitative evaluation index of crack sensitivity under different heat treatments.

10. The method for quantitatively evaluating the crack sensitivity of a Ti2AlNb material weld according to claim 1, characterized in that: In the step of comparing and analyzing the quantitative evaluation indexes of crack sensitivity under multiple groups of Ti2AlNb material plate welding parameters under different welding speeds and different heat treatments to obtain the quantitative results of the crack sensitivity of the Ti2AlNb material weld, the specific analysis process is as follows: Microhardness measurement and analysis of welded joints under different welding parameters and different post-weld heat treatment systems are carried out. When the hardness under different welding parameters and any parameters of different post-weld heat treatment systems is compared, the highest hardness indicates that the parameter is the optimal welding parameter or the optimal post-weld heat treatment system parameter.

Citation Information

Patent Citations

  • Annealing heat treatment process for eliminating stress after electronic beam welding of Ti2AlNb-based alloy

    CN104233141A

  • Method for evaluating hot wire TIG welding crack sensitivity

    CN108526658A

  • Evaluation method for crack sensitivity of metal material in additive manufacturing process

    CN109507194A

  • Comprehensive evaluation method for welding hot crack sensitivity

    CN112432862A

  • Welding filling material solidification crack sensitivity evaluation method and device

    CN114002391A